Perfluoroalkylated derivatives of 6-deoxy-6-ethylamino-D-galactose, 1-deoxy-1-methylamino-D-glucitol, and 1-amino-1-deoxy-D-glucitol: syntheses, hemocompatibility, and effect on perfluorocarbon emulsion - Kaplánek, Robert; Polák, Radek; Paleta, Oldrich; Kefurt, Karel; Moravcová, Jitka; Krenová, Iva; Kodícek, Milan (Carbohydrate research, 2010)
N-polyfluoroalkyl derivatives of 6-deoxy-6-ethylamino-1,2;3,4-di-O-isopropylidene-alpha-D-galactopyranose (8-10), 1-deoxy-1-methylamino-D-glucitol (13-15), and 1-amino-1-deoxy-D-glucitol (16-18), all possessing perfluoroalkyl segment, were prepared using nucleophilic epoxide ring opening of 2-[(perfluoroalkyl)methyl]oxiranes 1-3. Co-emulsifying properties and hemolytic activity of the new perfluoroalkylated amphiphiles were tested. Both types of the polyol derivatives 8-10 and 13-18 generally displayed good to excellent co-emulsifying properties on testing on perfluorodecalin/Pluronic F-68 microemulsions. Mono-perfluoroalkylated compounds 8-10 and 13-15 displayed high hemolysis, whereas acyclic bis-perfluoroalkylated compounds 16-18 were non-hemolytic even for short perfluorobutyl segment (16). The properties were generally improving with increasing perfluoroalkyl chain length.
Keywords: Morpholines; morfoliny; sorbitol; emulze; Hydrocarbons, Fluorinated; erytrocyty; Methylamines; lidé; Poloxamer; Fluorocarbons; ethylaminy; Erythrocytes; methylaminy; galaktosa; Ethylamines; fluorované uhlovodíky; Galactose; Emulsions; fluorokarbony; poloxamer; Sorbitol; Humans